Buscando la forma más eficaz de encontrar información - Borrego, Ángel (Anuario ThinkEPI, 2015)
Reseña del informe: Schonfeld, Roger C. (2014). Does discovery still happen in the library? Roles and strategies for a shifting reality. Ithaka S+R. http://sr.ithaka.org/blog-individual/does-discoverystill-happen-library-roles-and-strategies-shiftingreality